2015
DOI: 10.1093/epolic/eiv002
|View full text |Cite
|
Sign up to set email alerts
|

Global liquidity through the lens of monetary aggregates

Abstract: This paper examines how the financial activities of non-financial corporates (NFCs) in international markets potentially affects domestic monetary aggregates and financial conditions. Monetary aggregates reflect, in part, the activities of NFCs, who channel capital market financing into the domestic banking system, thereby influencing funding conditions and credit availability. Periods of capital inflows are also those when the domestic currency is appreciating, and such periods of rapid exchange rate apprecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 6 publications
0
45
0
Order By: Relevance
“…In column 3, the elasticity of holdings of liquid financial assets to bond issuance in the high spread regime is twice the elasticity in the low spread regime. 8 So far, we have established that emerging market firms that issue in foreign currency tend to hold more liquid financial assets and that the relationship between bond issuances and holdings of liquid financial assets is increasing in the spread between local deposit rates and the cost of borrowing in the US. We also showed that the e §ect of spreads is quantitatively large but not statistically significant.…”
Section: Bond Issuance and Holdings Of Liquid Financial Assetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In column 3, the elasticity of holdings of liquid financial assets to bond issuance in the high spread regime is twice the elasticity in the low spread regime. 8 So far, we have established that emerging market firms that issue in foreign currency tend to hold more liquid financial assets and that the relationship between bond issuances and holdings of liquid financial assets is increasing in the spread between local deposit rates and the cost of borrowing in the US. We also showed that the e §ect of spreads is quantitatively large but not statistically significant.…”
Section: Bond Issuance and Holdings Of Liquid Financial Assetsmentioning
confidence: 99%
“…Turner (2013) highlights the shift from bank financing to bond financing, particularly for emerging economies. Chung et al (2014) document the importance of this trend in terms of overall global liquidity and discuss the potential ramifications for financial stability. Powell (2014) considers the case of four large Latin American economies (Brazil, Chile, Colombia and Mexico) and documents a strong increase in issuance from non-financial firms, particularly in US dollars.…”
Section: Introductionmentioning
confidence: 98%
“…The empirical literature also points out that changes in narrow money aggregates, such as M2, may affect the buoyancy of banks' cross-border lending, although the exact channel for this is unclear. One argument may be that the growth in some components of broad money measures, such as wholesale or non-financial enterprises' deposits, can complement leverage measures in explaining bank risk as they indicate the relative ease of funding conditions (Hahm et al, 2013;Chung et al, 2014).…”
Section: B What Are the Determinants Of Global Liquidity?mentioning
confidence: 99%
“…Amounts outstanding increased after the crisis for all regions, but especially for Latin America. Chung et al (2013) highlight the relevance of monetary aggregates as a potential indicator of the channel through which offshore issuance of emerging market firms may influence domestic financial conditions. For firms that straddle the border, their financial activities are likely to leave an imprint on the domestic financial system hosting its headquarters.…”
Section: Second Phase Of Global Liquiditymentioning
confidence: 99%
“…If the firm issues debt offshore in FCY but accumulates liquid financial assets in domestic currency-in the form of claims on domestic banks or in the shadow banking system in the headquarter economythen keeping track of the firm's corporate deposits and short-term financial assets will give an indirect indication of its overseas financial activities and hence the broad financial conditions that prevail in international capital markets. Chung et al (2013) show that external financial conditions are reflected in the monetary aggregates of capital-recipient economies through the increased size of corporate deposits, as measured by the IMF's International Financial Statistics (IFS). As the firm will borrow more under permissive financial conditions, we would expect to see the conjunction of both the firm's increased indebtedness and greater holdings of cash and short-term investments on the consolidated balance sheet.…”
Section: Second Phase Of Global Liquiditymentioning
confidence: 99%